The Influence of Siblingships in a Person’s Self-regulation Process (Universitas Negeri Semarang, 2019)
This study presents the ways self regulation exists in the siblingship. How the older sibling influence the decision making towards the younger sibling or vice versa. In this case the decision making is based on where they study. These siblings are in the same university even they are in the same study program. This paper observes how they are affected to each other while they are in the same school. This paper uses interview as the method. In the findings will be revealed why they decide to be in the same university and in the same study program.